PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN SISA LEBIH PEMBIAYAAN ANGGARAN TERHADAP BELANJA MODAL PADA KOTA DAN KABUPATEN DI PULAU KALIMANTAN - Ida Mentayani; - Rusmanto (Universitas Trunojoyo Madura, 2013)
This aimed of this research is to provide empirical evidence about influenceof the General Allocation Fund (DAU), Local Own Revenue (PAD), FinancingSurplus Budget (SiLPA) on the Capital Expenditure districts/cities in IslandBorneo. The sample used in this study were 46 districts/cities in Island Borneotaken from the Report of Actual Income and Expenditure Budget (budget) fromthe years of 2010-2012. Analysis tool used in this study is multiple linierregression with a t-test, f-test, and test the coefficient of determination. The results of this research indicate that partial General Allocation Fund(DAU) Local Own Revenue (PAD) had no significant influence on the CapitalExpenditure. Meanwhile, Financing Surplus Budget (SiLPA) has significantinfluence on the Capital Expenditure. Simultaneously the General AllocationFund (DAU), Local Own Revenue (PAD), Financing Surplus Budget (SiLPA)significant influence on the Capital Expenditure districts/cities in IslandBorneo.